2015
DOI: 10.1017/s0033291714003109
|View full text |Cite
|
Sign up to set email alerts
|

Investigating genetic and environmental contributions to adolescent externalizing behavior in a collectivistic culture: a multi-informant twin study

Abstract: Chinese adolescents' Ext was moderately influenced by genetic factors. AGG and RB had moderate independent genetic and non-shared environmental influences, and thus constitute etiologically distinct dimensions within Ext in Chinese adolescents. The heritability of AGG, in particular, was smaller in Chinese adolescents than suggested by previous data obtained on Western peers. This study suggests that the collectivistic cultural values and Confucianism philosophy may attenuate genetic potential in Ext, especial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 33 publications
(39 reference statements)
1
13
0
Order By: Relevance
“…Our univariate analyses similarly demonstrated that our heritability values are similar to those of previous studies, especially for RB and AGG (Chen, Yu, Zhang, Li, & McGue, 2015;Porsch et al, 2016). For sleep duration, our estimate of genetic influence was on the higher end of the wide span of heritability estimates for children found in the literature, where values from .31 to .71 have been reported (Brescianini et al, 2011;Gregory et al, 2006).…”
Section: Discussionsupporting
confidence: 89%
“…Our univariate analyses similarly demonstrated that our heritability values are similar to those of previous studies, especially for RB and AGG (Chen, Yu, Zhang, Li, & McGue, 2015;Porsch et al, 2016). For sleep duration, our estimate of genetic influence was on the higher end of the wide span of heritability estimates for children found in the literature, where values from .31 to .71 have been reported (Brescianini et al, 2011;Gregory et al, 2006).…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, the need for social desirability may impede participants from disclosing their impulsive dispositions (detected with FS), which are typically associated with externalizing behaviors (54). This outcome could be more apparent in a collectivistic culture, which encourages social affiliation and leads to lower acceptability of externalizing behaviors (55). We strongly recommend that future studies examine the wording of the Fun Seeking subscale and other problematic items.…”
Section: Discussionmentioning
confidence: 99%
“…Proactive aggression showed slightly higher heritability estimates (32–48%) than reactive aggression (20–43%) [Baker et al, ; Tuvblad et al, ]. Highest, but strongly culturally variable, heritability estimates (29–68%) were obtained for the aggression subscale of the CBCL [Burt and Klump, ; Chen et al, ], which does not differentiate between reactive and proactive forms of aggression, and contains several items on physical aggression. The latter also shows relatively high heritability when assessed by other scales (38–60%) [Yeh et al, ; Lacourse et al, ].…”
Section: Methodsmentioning
confidence: 99%